“Marriage Is Perseverance”: Structural Violence, Culture, and AIDS in Malawi - Hayes, Nicole C. (Anthropologica, 2016)
This article uses contemporary Malawian proverbs about gender as a window on connections between structural violence, culture, and AIDS in Malawi. Malawi's colonial and post-colonial history forms the backdrop for considerations of Malawi's changing sexual landscape. The author argues that Malawi's legacy of structural violence, particularly the colonial introduction of male labour migration and massive gender inequalities, irrevocably altered Malawian gender roles. Any attempt to explain Malawi's high rate of AIDS must therefore consider how structural violence became entwined with cultural norms in the production of a competitive sexual economy based on multiple concurrent partner and transactional sex.